EFFECT OF MELATONIN AND VITAMIN E AS ANTIOXIDANTS ON BODY WEIGHT, CARCASS TRAITS OF AWASSI LAMBS FED A HIGH-ENERGY AND NORMAL DIET - Kanyar I. M.; F. Karadaş (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This experiment was carried out to evaluate the effects of vitamin E (Alpha tocopherol acetate) supplementation and melatonin implants on growth performance, and meat quality traits of Awassi male lambs fed by a high and normal energy concentrated diet in Iraq. Lambs were divided equally to two main groups to be fed either high or normal energy diet ,and each of them divided in to five treatment, the first as a control (T1,T6),two level of melatonin (18, 36mg/lamb) were applied to (T2,T3,T7,T8) and two level of vitamin E (200,400mg/lamb/day) to (T4,T5,T9,T10).All animals were slaughtered at the end of the fattening period. Lambs received 400 g/day vitamin E with high energy diet surpassed significantly other treatment in final weight gain, vitamin E 400 mg/lamb/day and melatonin 18-36 mg/lamb at day 14 of storage increased retail color stability. enhanced meat color parameters. Melatonin implantation 18 mg/lamb, 36 mg /lamb significantly at day 7 of storage reduced MDA value, but at day 14 of storage vitamin E 200 and 400 mg/day/lamb reduced significantly MDA value of the Muscle Longissimus dorsi (LD) during storage.